Outspoken : conversations on church communication - Schraeder, Tim; Hendricks, Kevin D.; Center for Church Communication (Los Angeles, California : Center for Church Communication, 2011)
A guide for church leaders to improve the communication of their message by leveraging new media to effectively connect people with the gospel.
General communication -- Leadership -- Branding -- Design -- Words and stories -- Technology -- Creativity -- Personal growth -- Outreach.
Title from cover.
Keywords: Church marketing; Church growth; Internet in church work